Penyuluhan Hukum Tentang Dampak dan Pencegahan Perkawinan Dini di Kalangan Remaja - Mohammad Hifni; Winda Putri Julianah; Chindy Nurul Fadilah; Muhammad Solihin; Wira Pratama (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2026)
Early marriage is a social and legal issue that still frequently occurs in Indonesia and has significant impacts on health, education, and socio-economic aspects. Although the minimum age for marriage has been regulated under Undang-Undang Nomor 16 Tahun 2019 tentang Perkawinan, the practice of early marriage remains prevalent due to low legal awareness, as well as economic, cultural, and social environmental factors. This community service activity aims to increase adolescents’ understanding and legal awareness regarding the impacts and prevention of early marriage. The method used is legal counseling with an educative and participatory approach targeting adolescents aged 15–18 years. The results indicate a significant improvement in participants’ understanding of legal regulations, the negative impacts of early marriage, and the importance of delaying marriage age. Furthermore, there is a positive change in participants’ attitudes, with a greater focus on education and future planning. Therefore, legal counseling proves to be an effective preventive effort in reducing the rate of early marriage among adolescents.